2007
DOI: 10.1016/j.brainres.2006.10.081
|View full text |Cite
|
Sign up to set email alerts
|

Delayed suppression of hippocampal cell proliferation in rats following inescapable shocks

Abstract: Adult Sprague-Dawley rats were exposed to a single session of 100 inescapable tail shocks (IS). Bromodeoxyuridine (BrdU) was administered 1 h, 2 d or 7 d later and hippocampal cell proliferation (CP) was assessed after a two-hour survival period. Measures of plasma corticosterone (CORT) levels were also obtained. Despite a large increase in CORT immediately following IS, no associated change in CP was observed. In fact, the only significant change in CP was seen 7 days after IS, at a time when CORT was unchang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…However, despite the convincing relevance of these data, some recent reports have put emphasis on the complex relationships that may exist between corticosterone secretion and cell proliferation. Various stressful experiences which activate HPA axis may affect differentially hippocampal cell proliferation, and, in particular, a session of repeated inescapable shocks that produced an immediate increase in plasma corticosterone levels was found to cause a significant suppression of hippocampal cell proliferation only after a 7 day delay following the stress session [62]. Because corticosterone levels had returned to basal values after such a long time interval, these data suggested that the postulated direct causal link between HPA activation and hippocampal neurogenesis inhibition might occur under some but not all repeated stress conditions.…”
Section: Neurogenesis and Mood Disordersmentioning
confidence: 98%
See 1 more Smart Citation
“…However, despite the convincing relevance of these data, some recent reports have put emphasis on the complex relationships that may exist between corticosterone secretion and cell proliferation. Various stressful experiences which activate HPA axis may affect differentially hippocampal cell proliferation, and, in particular, a session of repeated inescapable shocks that produced an immediate increase in plasma corticosterone levels was found to cause a significant suppression of hippocampal cell proliferation only after a 7 day delay following the stress session [62]. Because corticosterone levels had returned to basal values after such a long time interval, these data suggested that the postulated direct causal link between HPA activation and hippocampal neurogenesis inhibition might occur under some but not all repeated stress conditions.…”
Section: Neurogenesis and Mood Disordersmentioning
confidence: 98%
“…Because corticosterone levels had returned to basal values after such a long time interval, these data suggested that the postulated direct causal link between HPA activation and hippocampal neurogenesis inhibition might occur under some but not all repeated stress conditions. Thus, for such inescapable shock-evoked stress, some kind of an ''incubation period'' (with the implication of intermediate factors which remain to be identified) should be necessary for allowing its negative influence on hippocampal cell proliferation [62].…”
Section: Neurogenesis and Mood Disordersmentioning
confidence: 99%
“…Distinct stressful experiences, which all activate the HPA axis, were thus shown to differentially affect hippocampal cell proliferation (see Paizanis et al, 2007). Furthermore, some kind of an ''incubation period'' (implicating unknown intermediate factors) appeared to be necessary to observe the deleterious effects of stress on hippocampal cell proliferation (Fornal et al, 2007).…”
Section: Neurotrophic Factors Beyond the Hpa/5-ht Interactionsmentioning
confidence: 98%
“…Acute exposure to electric shock decreases cell proliferation in the dentate gyrus of adult rats (Malberg & Duman, 2003). One study showed a delayed decrease in cell proliferation seven days following shock trials, after the increases in glucocorticoid levels had gone back down to baseline (Fornal et al, 2007), suggesting a more complicated relationship may exist between electric shock and cell proliferation.…”
Section: Effects Of Stress On Adult Neurogenesismentioning
confidence: 99%